THE RELATIONSHIP BETWEEN COMMUNICATION ATMOSPHERE AND WORK MOTIVATION - Helen Sitorus Vanhurk Sriwati Ningsih Sitorus (JURNAL PROINTEGRITA, 2019)
This research aims at finding the correlation the atmosphere of organization’s communication with employee’s work motivation of the staffs of Darma Agung University because the optimal work motivation of the staffs is main capital of the institution’s objective. Theory used in this research is S-O-R theory and Human Relation theory. Research method used is correlational methodin which the total population is 60 employees. Technique of collecting data was done by using observation, questionnaires and literature review. Based on research finding that was conducted in Darma Agung University, it can be concluded that the atmosphere of communication in Darma Agung University is categorized in to High level so that it gives effects on employees’ work motivation that is categorized into very high motivation. This is caused by the leaders of Darma Agung University notice the employees’ welfare in which the openness, trust and honesty are always done between the leaders and the employees, vice versa. High work motivation is also caused by each respondent wants to get the appreciation and will to be better than his peers. Research findings show that correlation coefficient (r) = 0.017, significance level (R < 0.05) means that there is a significant correlation between the atmosphere of organization’s communication and work motivation of the employees of Darma Agung University. It means that hypothesis on this research is accepted.